2005
DOI: 10.1111/j.1442-200x.2005.02084.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural comparison of the neurobehavioral characteristics of Chinese and Japanese neonates

Abstract: These results suggest that Japanese newborns habituated more readily to stimuli, and were less irritable than newborns in the Chinese sample. The infants in the two groups shared many similar neurobehavioral characteristics as well. The implications of these similarities and differences were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Field, Diego, Hernandez-Reif, Schanberg, & Kuhn, 2002), risk factors (e.g. Ohgi et al, 2003), effects of maternal substance use (Myers et al, 2003), inter-cultural studies (Loo, Ohgi, Zhu, Howard, & Chen, 2005), gender differences (Boatella-Costa, and intervention studies (Ohgi, Fukuda, Akiyama, & Gima, 2004). Considering the importance of assessing the psychometric properties of these factors, two lines of studies have emerged using: (1) confirmatory factorial analyses and (2) exploratory factorial analyses with comparison of the psychometric properties of the derived factor with the psychometric properties of the Lester et al (1982) factors.…”
Section: Introductionmentioning
confidence: 99%
“…Field, Diego, Hernandez-Reif, Schanberg, & Kuhn, 2002), risk factors (e.g. Ohgi et al, 2003), effects of maternal substance use (Myers et al, 2003), inter-cultural studies (Loo, Ohgi, Zhu, Howard, & Chen, 2005), gender differences (Boatella-Costa, and intervention studies (Ohgi, Fukuda, Akiyama, & Gima, 2004). Considering the importance of assessing the psychometric properties of these factors, two lines of studies have emerged using: (1) confirmatory factorial analyses and (2) exploratory factorial analyses with comparison of the psychometric properties of the derived factor with the psychometric properties of the Lester et al (1982) factors.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely related to inherent physiological robustness of infants who are more autonomically stable, and is consistent with previous findings in a Japanese sample. In that study, newborns that were more autonomically stable (showed less startles and were less susceptible to abnormal changes in skin colour, such as cyanosis or becoming pale) also tended to show clearer behavioural cues, and were more responsive to the mother at 1 month (Loo et al, 2005b).…”
Section: Discussionmentioning
confidence: 86%
“…Chinese babies were in the middle range of irritability and consolability, compared to Malay and Tamil newborns (Freedman & Freedman, 1969). A more recent cross-cultural comparison of the neurobehavioural characteristics of Chinese and Japanese newborns showed that although the infants in the two groups shared many similar characteristics, Chinese newborns habituated less readily to stimuli, and were more irritable compared to newborns in the Japanese sample (Loo et al, 2005b).…”
Section: Introductionmentioning
confidence: 90%